Social cohesion among Syrian and Turkish children, adolescents, and young adults in Turkey: Data from Turkey - Marta Parigi; Nitya Mittal; Sebastian Vollmer (Scientific Data)
Abstract This data set provides information about basic social-demographic characteristics and social cohesion among young Turkish nationals and Syrian refugees. Information on different dimensions of social cohesion such as belongingness, trust, altruism and social relations, along with socio-demographic information, was collected from a sample of 1305 adolescents and young adults (12–30 years), and 685 children (6–11 years). Data was collected through field interviews between November 2018 – January 2019 in Ankara, Istanbul, and in the bordering cities of Mardin, Gaziantep, Hatay and Şanlıurfa. The sample was selected using a cluster randomised design among the participants of the “Education Program for Syrian Refugees and Host Communities” (BILSY) program conducted by the German Corporation for International Cooperation (GIZ) in Turkey.